1984
DOI: 10.1080/15298668491399361
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Control of Occupational Hazards Associated with the Use of Spirit Duplicators

Abstract: A Health Hazard Evaluation was conducted by the National Institute for Occupational Safety and Health (NIOSH) to determine if vapors from duplicating fluid (99% methyl alcohol) used in direct-process spirit duplicating machines were causing adverse health effects among teacher aides, or had been responsible for the deaths of three former teacher aides. Death certificates and autopsy data were obtained and evaluated. A self-administered symptom questionnaire was distributed to current teacher aides (exposed gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…In contrast to acute toxicity, there is limited information on chronic methanol toxicity. Chronic exposure at levels >260 mg/m 3 ranging from 1 to 8 h/day, up to 5 days/week for up to 3 years has been reported to cause symptoms of headache, dizziness, lightheadedness, blurred vision, and nausea and upset stomach (Frederick, Schulte, & Apol, 1984). Chronic exposures may result in irreversible optic damage (Kavet & Nauss, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to acute toxicity, there is limited information on chronic methanol toxicity. Chronic exposure at levels >260 mg/m 3 ranging from 1 to 8 h/day, up to 5 days/week for up to 3 years has been reported to cause symptoms of headache, dizziness, lightheadedness, blurred vision, and nausea and upset stomach (Frederick, Schulte, & Apol, 1984). Chronic exposures may result in irreversible optic damage (Kavet & Nauss, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Amblyopia from vapor inhalation in occupational exposure to methanol (visually impaired) and approximately 100 deaths were reported until 1912 [ 1 , 33 ]. Most patients had been exposed to methanol vapor (300 mg/L) [ 34 , 35 ]. Wood heel manufacturing industry workers were exposed to a concentration of methanol vapor ranging from 160 to 780 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…There is some evidence from epidemiological studies of workers exposed to methanol from duplicating machines that repeated sublethal doses (less than 0.3 g/kg body weight and above the TLV of 200 ppm) may cause headache, dizziness, nausea, and blurred vision, indicating that methanol exposure can result in CNS depression (52,53). The exposure duration in the latter study was reported to range from 1 hr/day for 1 day/week to 8 hr/day for 5 days/ week and had presumably been occurring for about 3 years.…”
Section: Repeated Exposure Studiesmentioning
confidence: 99%